Akupresure untuk Mengatasi Dismenore pada Remaja Putri: Acupressure to Overcome Dysmenorrhea in Teenager - Khamidah; Ida Sofiyanti (Journal of Holistics and Health Sciences (JHHS), 2023)
Dysmenorrhea is a condition that occurs during menstruation which can cause disruption of activities and requires treatment if the symptoms are felt to be severe, and are indicated by pain or tenderness in the pelvic and abdominal areas, dizziness, nausea, vomiting, and diarrhea. Madrasah Tsanawiyah Ma'arif Nyatnyono with a total of 60 young women of which 19 young women experienced menstruation without dysmenorrhea and 38 young women experienced menstruation accompanied by dysmenorrhea. Treatments carried out by adolescents are sleeping, lying down, eating, watching cellphones, snacks, and traveling. An alternative non-pharmacological treatment of dysmenorrhea is acupressure which is easy to learn (practical), safe and free of charge and needs to be done independently. Acupressure is an emphasis on certain body meridian points clockwise for 30 rounds for 3-5 minutes. This study aims to determine the effect of acupressure to overcome dysmenorrhea in young women at Madrasah Tsanawiyah Ma'arif Nyatnyono, West Ungaran District. This type of research uses a pre-experimental research design with a one group pretest posttest design. The population in this study amounted to 60 young women, with a sample of 38 respondents using purposive sampling. The instrument used was the SOP and the Numerical Rating Scale (NRS) questionnaire. Data analysis used the Wilcoxon test. The results showed that the average dysmenorrhea pain scale before acupressure was performed was 3.95 points with a minimum value of 2 and a maximum value of 6 and after acupressure was performed, namely 1.68 points with a minimum value of 0 and a maximum value of 3. There was a significant effect between acupressure to overcome dysmenorrhea in young women at Madrasah Tsanawiyah Ma'arif Nyatnyono, West Ungaran District, this is indicated by the P value of 0.000 which is less than 0.05 which means Ho is rejected and Ha is accepted. There is a significant effect between acupressure to overcome dysmenorrhea in young women at Madrasah Tsanawiyah Ma'arif Nyatnyono, West Ungaran District.   ABSTRAK Dismenore adalah suatu kondisi yang terjadi saat menstruasi dimana bisa menyebabkan terganggunya kegiatan serta membutuhkan perawatan apabila gejala yang dirasakan berat, serta ditunjukkan melalui rasa sakit ataupun nyeri pada area panggul serta perut, pusing, mual, muntah, dan diare. Madrasah Tsanawiyah Ma’arif Nyatnyono sejumlah 60 remaja putri yang mana diantaranya 19 remaja putri mengalami menstruasi tanpa disertai dismenore dan 38 remaja putri diantaranya mengalami menstruasi dengan disertai dismenore. Penanganan yang dilakukan oleh remaja yaitu dengan tidur, rebahan, makan, menonton HP, jajan, dan jalan-jalan. Alternatif penanganan dismenore secara non farmakologi yaitu dengan akupresure yang mudah dipelajari (praktis), aman dan tanpa biaya serta perlu dilakukan secara mandiri. Akupresure adalah penekanan pada titik meridian tubuh tertentu searah jarum jam sebanyak 30 putaran selama 3 – 5 menit. Penelitian ini bertujuan mengetahui pengaruh akupresure untuk mengatasi dismenore pada remaja putri di Madrasah Tsanawiyah Ma’arif Nyatnyono Kecamatan Ungaran Barat. Jenis penelitian ini menggunakan jenis penelitian pre eksperimental rancangan one group pretest posttes design. Populasi pada penelitian ini berjumlah 60 remaja putri, dengan sampel 38 responden menggunakan purposive sampling. Instrument yang digunakan SOP dan kueisoner Numerik Rating Scale (NRS). Analisa data menggunakan uji Wilcoxon. Hasil penelitian menunjukkan rata rata skala nyeri dismenore sebelum dilakukan akupresure yaitu sebesar 3,95 poin dengan nilai minimum 2 dan nilai maximum 6 dan sesudah dilakukan akupresure yaitu sebesar 1,68 poin nilai minimum 0 dan nilai maximum 3. Ada pengaruh yang signifikan antara akupresure untuk mengatasi dismenore pada remaja putri di Madrasah Tsanawiyah Ma’arif Nyatnyono Kecamatan Ungaran Barat, hal ini ditunjukkan dengan hasil P value sebesar 0,000 yang kurang dari 0,05 yang berarti Ho ditolak dan Ha diterima. Ada pengaruh yang signifikan antara akupresure untuk mengatasi dismenore pada remaja putri di Madrasah Tsanawiyah Ma’arif Nyatnyono Kecamatan Ungaran Barat.